Experiences and lessons learned from two virtual, hands-on microbiome bioinformatics workshops. - Matthew R Dillon; Evan Bolyen; Anja Adamov; Aeriel Belk; Emily Borsom; Zachary Burcham; Justine W Debelius; Heather Deel; Alex Emmons; Mehrbod Estaki; Chloe Herman; Christopher R Keefe; et al. (PLoS Computational Biology)
In October of 2020, in response to the Coronavirus Disease 2019 (COVID-19) pandemic, our team hosted our first fully online workshop teaching the QIIME 2 microbiome bioinformatics platform. We had 75 enrolled participants who joined from at least 25 different countries on 6 continents, and we had 22 instructors on 4 continents. In the 5-day workshop, participants worked hands-on with a cloud-based shared compute cluster that we deployed for this course. The event was well received, and participants provided feedback and suggestions in a postworkshop questionnaire. In January of 2021, we followed this workshop with a second fully online workshop, incorporating lessons from the first. Here, we present details on the technology and protocols that we used to run these workshops, focusing on the first workshop and then introducing changes made for the second workshop. We discuss what worked well, what didn't work well, and what we plan to do differently in future workshops.